Clinical Characteristics of Down Syndrome with Congenital Heart Disease - Safira Azzahra; Agustini Utari; Anindita Soetadji (Faculty of Medicine Universitas Indonesia, 2022)
Down syndrome (DS) or trisomy 21, causes overexpression of genes in most affected organs, including congenital heart disease (CHD). CHD is found in 40-60% of people with DS, with a high mortality rate in early life.Clinical signs and symptoms often found are essential indicators of early diagnosis of CHD. This study aimed todetermine the clinical characteristics of DS children with and without CHD. This study was a retrospective study.The study was conducted on August until October 2019. We took data from the inpatient and outpatient medicalrecords database for the years 2017-2019 in Dr. Kariadi Hospital, Semarang, Indonesia. Some informationincludes clinical signs and symptoms, nutritional status, comorbidities, and frequency of hospitalization in amonth were collected. A total of 66 patients were diagnosed with DS, consisting of 44 DS patients with CHDand 22 DS patients without CHD. There were no differences in nutritional status, interrupted breastfeeding, chestretraction, respiratory rate, thyroid disorder, hearing abnormalities, acute otitis media, and obstructive sleepapnea in both groups (p> 0.05). There were significant differences in the clinical characteristics of cyanosis(p=0.005), heart murmur (p=<0.001), and frequency of acute respiratory tract infection in a year (p=<0.001), andfrequency of hospitalization per month (p=0.039) in DS children with and without CHD. In conclusion, we foundsignificant difference in clinical characteristic in DS children with and without CHD.